2010
DOI: 10.3109/08820538.2010.481239
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vessel Leakage (PVL): A New Angiographic Finding in Diabetic Retinopathy Identified with Ultra Wide-Field Fluorescein Angiography

Abstract: Untreated peripheral non-perfusion and late peripheral vascular leakage detected using ultra wide-field FA are associated with neovascularization in diabetic retinopathy. PVL may be associated with focal diabetic macular leakage in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…selected 1 or more images from each angiogram series during the arteriovenous phase (between 45 seconds and 2 minutes) and graded all 148 angiograms for the presence or absence of retinal nonperfusion of > _1 disc area, neovascularization (defined as focal leakage > _2 disc diameters), focal macular edema (defined as late hyperfluorescence > _500 mm diameter covering less than 75% of the macula), and diffuse macular edema (defined as late hyperfluorescence covering > _75% of the macula). 10,13 The best image was chosen based on the largest field of view and the greatest image clarity. Figure 1 illustrates typical findings encountered when grading.…”
Section: Methodsmentioning
confidence: 99%
“…selected 1 or more images from each angiogram series during the arteriovenous phase (between 45 seconds and 2 minutes) and graded all 148 angiograms for the presence or absence of retinal nonperfusion of > _1 disc area, neovascularization (defined as focal leakage > _2 disc diameters), focal macular edema (defined as late hyperfluorescence > _500 mm diameter covering less than 75% of the macula), and diffuse macular edema (defined as late hyperfluorescence covering > _75% of the macula). 10,13 The best image was chosen based on the largest field of view and the greatest image clarity. Figure 1 illustrates typical findings encountered when grading.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the seven-standard fields would have missed pathology shown on UWF FA images in 10% of eyes [30]. Other studies have demonstrated the association between peripheral retinal nonperfusion and the occurrence of neovascularization, macular ischemia, and diabetic mac-http://dx.doi.org/10.21561/jor.2016.1.1.1 ular edema (DME) [20,[31][32][33]. Another study suggested that UWF FA will be used to guide the management of DR [34].…”
Section: Clinical Applications Of Ultra-widefield Imaging Diabetic Rementioning
confidence: 99%
“…Ultra-widefield FA is available in the Optos system since the P200A model provides a high-resolution wide-angle angiographic module. Single capture using a 488-nm laser with a 500-nm barrier filter enables angiographic view of peripheral vascular structure, including perfusion status, leakage, and staining, which can be missed on the seven-standard fields of the Early Treatment Diabetic Retinopathy Study [17][18][19][20]. ICGA was recently added to the multimodal capabilities of the Optos.…”
Section: Ultra-widefield Imaging Modalitiesmentioning
confidence: 99%
“…12 The degree of peripheral nonperfusion has also been linked to increased diabetic macular edema (DME) in treatment-naĂŻve patients with diabetic retinopathy, 13 as well as more recalcitrant DME, as evidenced by a greater number of macular photocoagulation treatments and less reduction in central macular thickness on optical coherence tomography (OCT). 14 …”
Section: Diabetic Retinopathymentioning
confidence: 99%